أحكام جريمة الإجهاض بين الشريعة الإسلامية والقانون الجزائري - عطا الله, مسعودة; برجوح, يسرى (University of eloued جامعة الوادي, 2022)
"هذا البحث عبارة عن دراسة تحليلية مقارنة بين موقف القانون الجزائري وموقف الشريعة الإسلامية من جريمة الإجهاض. تعرضنا من خلال هذا البحث إلى تعريف الإجهاض، في الشريعة الإسلامية والقانون الجزائري. ثم تطرقنا إلى أنواع هذه الجريمة وحكمها في الشريعة الإسلامية وموقف القانون الجزائري حولها. ثم عرجنا بشيء من التفصيل حول أركان جريمة الإجهاض في الشريعة وقانون العقوبات الجزائري. ثم تكلمنا عن عقوبة الإجهاض في الشريعة والقانون الجزائري، ووسائل إثبات هذه الجريمة. ""This research is a comparative analytical study between the position of algerian law and the position of islamic sharia regarding the crime of abortion. Through this research, we presented a definition of abortion, in Islamic law and Algerian law. Then we touched on the types of this crime and its ruling in Islamic law and the position of Algerian law on it. Then we went in some detail about the pillars of the crime of abortion in Sharia and the Algerian Penal Code. Then we talked about the penalty for abortion in Sharia and Algerian law, and the means of proving this crime. "
مذكرة ماستر
Keywords: الإجهاض-الجنين -الشريعة الإسلامية-القانون الجزائري.; Miscarriage- fetus- islamic law- algerian law.